Nomad Tourism Development Strategy in Super Priorities Tourism Destinations Labuan Bajo - Rosianna Sianipar; Nova Bernedeta Sitorus; Juliana (Jurnal Mantik, 2022)
The purpose of this research is to examine tourism development and identify the application of nomadic tourism in destinations Labuan Bajo super priority tourism. This study also aims to determine strategies that can be used to develop nomadic tourism in tourist destinations Labuan Bajo's super priority. This study uses a qualitative method, presenting the data in words, descriptions and descriptions. In this case, the qualitative data in question are how to apply nomad tourism and its development in super tourist destinations Labuan Bajo priority. Nomad tourism is a new style of travel and has been very suitable for development since the Covid-19 Pandemic. Nomad tourism has a concept where tourists can stay for some time with movable amenities. Nomad tourism also has the potential to develop in many tourist destinations in Indonesia with a complete tourism component, one of which is Labuan Bajo. Labuan Bajo has the potential to develop nomad tourism because it has many good amenities with criteria star and non-star with different price levels. Travel concept nomads are in great demand by tourists of productive age, namely 35-55 years and have income and rely heavily on the latest information in determining travel activities. Labuan Bajo has the potential to be developed as a destination for travel to nomads and become one of the ways to increase return visits tourists to Labuan Bajo.